2018
DOI: 10.1371/journal.pone.0202129
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities and determinants of maternal health services in Shaanxi Province, Western China

Abstract: Prenatal health care interventions are effective ways to improve maternal and neonatal health. There have been few large investigations conducted on the inequalities in maternal health services utilization in Shaanxi Province of west China since the health care reform in 2009. This study examined the inequalities and determinants of maternal health services utilization in Shaanxi Province. A household survey was conducted from August to November in 2013. By using a multistage sampling method, local women aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 38 publications
4
30
0
Order By: Relevance
“…Although previous studies have shown that high-SES is a protective factor in using public health service among the migrants [12,16,17,[47][48][49], few explored from the perspective of inpatient services need among internal migrants in China. The present study also has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have shown that high-SES is a protective factor in using public health service among the migrants [12,16,17,[47][48][49], few explored from the perspective of inpatient services need among internal migrants in China. The present study also has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…In China existing research on the healthcare reform impacts primarily focuses on prenatal visits, hospital delivery or postnatal visits separately. Recent studies have evaluated socio-economic inequalities and found socioeconomic determinants of prenatal and postnatal visits [17][18][19], explored influence of health policy on improving the utilisation of hospital delivery [20], prenatal or postnatal visits [21], fewer studies explore the utilisation of CMHS. To date, there has been some research exploring the determinants, effects, value, measurement of CMHS in LMICs outside of China: in Lao PDR [22], Nepal [23], Tanzania [10], South Africa [11], Cambodia [24].…”
Section: Introductionmentioning
confidence: 99%
“…The major contribution of this study was that we sought to identify the relationship between individual's SES and unmet inpatient service among internal migrants. Although previous studies have shown that high-SES is a protective factor in using public health service among the migrants [9,15,17,19,38,39], but few studies have explored the association between SES and unmet inpatient services among internal migrants in China. However, this study also had several limitations.…”
Section: Discussionmentioning
confidence: 99%